2010
DOI: 10.4038/slja.v18i2.2446
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and compliance with regard to universal precautions and other standard practices to reduce blood-borne infections among anaesthetists at the National Hospital of Sri Lanka

Abstract: Anaesthetists are a group of doctors who are at a higher occupational risk of contracting blood borne infections as they perform many invasive procedures. Practice of Universal Precautions (UP) is vital in reducing the risk of transmission. The objective of this study was to assess the knowledge and compliance among anaesthetists of the National Hospital of Sri Lanka (NHSL) on UP and related issues. Information was collected from 97 anaesthetists at the NHSL using a structured questionnaire. Knowledge and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…We found that those who had good knowledge scores adhered to the standard precautions well, however, their education level or the experience did not significantly associate with good practice. Similar to our study, the education level had no association with the adherence to the standard precautions among radiographers in a tertiary care hospital of Sri Lanka [17]. However, a Sri Lankan study conducted among the nursing staff at the same setting concluded that the junior nurses were more compliant on the standard precautions than the senior nursing staff, probably since the former have updated their knowledge recently [18].…”
Section: Discussionsupporting
confidence: 70%
“…We found that those who had good knowledge scores adhered to the standard precautions well, however, their education level or the experience did not significantly associate with good practice. Similar to our study, the education level had no association with the adherence to the standard precautions among radiographers in a tertiary care hospital of Sri Lanka [17]. However, a Sri Lankan study conducted among the nursing staff at the same setting concluded that the junior nurses were more compliant on the standard precautions than the senior nursing staff, probably since the former have updated their knowledge recently [18].…”
Section: Discussionsupporting
confidence: 70%